2010
DOI: 10.1124/mol.110.067611
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Dual Pseudosymmetric Solute Translocation Pathways in Human P-Glycoprotein

Abstract: The human multispecific drug efflux transporter P-glycoprotein (P-gp) causes drug resistance and modulates the pharmacological profile of systemically administered medicines. It has arisen from a homodimeric ancestor by gene duplication. Crystal structures of mouse MDR1A indicate that P-gp shares the overall architecture with two homodimeric bacterial exporters, Sav1866 and MsbA, which have complete rotational symmetry. For ATP-binding cassette transporters, nucleotide binding occurs in two symmetric positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 36 publications
6
86
3
Order By: Relevance
“…Co-crystal structure of mouse P-gp with several QZ-59 cyclopeptide inhibitor derivatives [21], and PBDE-100 pesticide [31] allowed identification of several key amino acids in the substrate or modulator binding pocket of mouse P-gp. We further used published bioinformatic and mutagenesis studies, and generated a list of key amino acids that interact with different substrates or modulators [11, 17, 20, 32–34]. Additionally, we generated a homology model of human P-gp based on the refined mouse P-gp crystal structure [10] and further selected amino acids based on their position and orientation with respect to the drug-binding pocket.…”
Section: Resultsmentioning
confidence: 99%
“…Co-crystal structure of mouse P-gp with several QZ-59 cyclopeptide inhibitor derivatives [21], and PBDE-100 pesticide [31] allowed identification of several key amino acids in the substrate or modulator binding pocket of mouse P-gp. We further used published bioinformatic and mutagenesis studies, and generated a list of key amino acids that interact with different substrates or modulators [11, 17, 20, 32–34]. Additionally, we generated a homology model of human P-gp based on the refined mouse P-gp crystal structure [10] and further selected amino acids based on their position and orientation with respect to the drug-binding pocket.…”
Section: Resultsmentioning
confidence: 99%
“…How interactions between drugs at the level of transport are related to the structure of the Pgp binding pocket in molecular terms is not well understood. However, the location of two pseudo-symmetric translocation pathways through the protein has recently been reported (Parveen et al, 2011). The complication of multiple binding sites and the interactions between them has not really been addressed in cell-based assays for Pgp substrates and inhibitors (Zolnerciks, Booth-Genthe, Gupta, Harris, & Unadkat, 2011), and may require the use of several reference compounds, which is not practical where many drugs are to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…(32, 33, 75, 76)]. Mutagenesis studies suggested that the pocket was located at the interface between the two TM halves (77), and this was later confirmed by photoaffinity labeling in conjunction with MS (78, 79). The first X-ray crystal structures of mouse Pgp in an inward-facing conformation appeared in 2009 (34).…”
Section: Pgp Structurementioning
confidence: 93%